An integrated system for field analysis of Cd(ii) and Pb(ii) via preconcentration using nano-TiO2/cellulose paper composite and subsequent detection with a portable X-ray fluorescence spectrometer. Issue 11 (22nd January 2016) - Lin, Xiaofeng; Li, Shun-Xing; Zheng, Feng-Ying
Abstract : An integrative field analytical system was developed for the determination of Pb(ii ) and Cd(ii ). Abstract : An integrative field analytical system was developed for the determination of Pb(ii ) and Cd(ii ). The system was based on the hyphenation of a preconcentration process with a portable X-ray fluorescence spectrometer. Preconcentration was accomplished with a composite consisting of TiO2 and a cellulose film (TCP) which was prepared by immobilizing TiO2 on cellulose filter paper. TCP is shown to be an adsorbent with high adsorption capacity, i.e., more than 254 μg per piece and 259 μg for Pb(ii ) and Cd(ii ), respectively. Under the optimum adsorption conditions, the best adsorption ratios of Pb(ii ) and Cd(ii ) were more than 95.5% and 94.4%, respectively. The preconcentration of Pb(ii ) and Cd(ii ) was not adversely affected by other metals ions and humic acid. Pb(ii ) and Cd(ii ) were then directly quantified by XRF. The calibration plots for both Pb(ii ) and Cd(ii ) were linear in the range from 1.0 to 50.0 μg L −1 . The detection limits (3 σ ; for n = 11) for Pb(ii ) and Cd(ii ) were 0.69 and 0.51 μg L −1, respectively, and the levels of quantification were 2.30 and 1.71 μg L −1, respectively. The preconcentration factor was 10 3 . Concentrations of Pb(ii ) and Cd(ii ) in drinking water and river waters were determined and found to be in agreement with ICP-MS assays.